The need analysis of BIPA speaking materials and modules for foreign athletes - Ray Ardi Putra; Nuny Sulistyani Idris; Suci Sundusiah (Inovasi Kurikulum, 2024)
BIPA (Indonesian Language for Foreign Speakers) is very popular among the international community. This situation can be seen in many foreign students studying Indonesian. BIPA students come from various backgrounds, including business, health, military, academics, and sports. The BIPA sports learning module has also become necessary for BIPA sports students. This is driven by the interest of foreign athletes in studying BIPA, such as Danish badminton players who want to learn Indonesian. This research is an analysis of research and development (RnD) needs with the ADDIE concept, which will produce a product that is developed and validated for the world of education, intending to renew or innovate the development of existing educational products. There are five RnD research procedures with the ADDIE analysis concept: needs, planning and design, development, implementation, and evaluation. Analysis steps were carried out on BIPA students to get responses regarding Indonesian language needs. The type of product being developed is an open BIPA speaking skills module for BIPA athletes learners. However, this research analyzes the need to develop BIPA modules for athletes. Analysis of needs for developing BIPA modules is necessary for BIPA teachers to provide an overview of what modules should be developed. AbstrakBahasa Indonesia untuk Penutur Asing (BIPA) saat ini sangat populer di kalangan masyarakat internasional. Situasi ini terlihat dari banyaknya pelajar luar negeri yang belajar bahasa Indonesia. Pemelajar BIPA berasal dari berbagai latar belakang, antara lain bisnis, kesehatan, militer, akademik, dan olahraga. Modul pembelajaran BIPA olahraga juga sudah menjadi kebutuhan bagi Pemelajar BIPA olahraga. Hal ini didorong oleh minat olahragawan mancanegara untuk mempelajari BIPA, seperti pebulu tangkis Denmark yang ingin belajar bahasa Indonesia. Penelitian ini merupakan analisis kebutuhan penelitian dan pengembangan (RnD) dengan konsep ADDIE yang akan menghasilkan suatu produk yang dikembangkan dan divalidasi bagi dunia pendidikan, dengan tujuan memperbaharui atau menginovasi pengembangan produk pendidikan yang sudah ada. Terdapat lima prosedur penelitian RnD dengan konsep ADDIE, yaitu analisis kebutuhan, perancangan dan desain, pengembangan, implementasi, dan evaluasi. Langkah analisis dilakukan terhadap mahasiswa BIPA untuk mendapatkan tanggapan mengenai kebutuhan bahasa Indonesia. Adapun jenis produk yang dikembangkan yaitu modul ajar BIPA keterampilan berbicara bagi pembelajar BIPA olahragawan. Namun, dalam penelitian ini berfokus pada analisis kebutuhan pengembangan modul BIPA untuk para olahragawan.Analisis kebutuhan untuk pengembangan modul ajar BIPA menjadi suatu kebutuhan bagi para pengajar BIPA agar dapat memberikan gambaran seperti apa modul sebaiknya dikembangkan.Kata Kunci: Bahasa Indonesia; BIPA; modul; olahragawan